2017
DOI: 10.1038/ncomms15099
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution in myelodysplastic syndromes

Abstract: Cancer development is a dynamic process during which the successive accumulation of mutations results in cells with increasingly malignant characteristics. Here, we show the clonal evolution pattern in myelodysplastic syndrome (MDS) patients receiving supportive care, with or without lenalidomide (follow-up 2.5–11 years). Whole-exome and targeted deep sequencing at multiple time points during the disease course reveals that both linear and branched evolutionary patterns occur with and without disease-modifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
3
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 42 publications
(51 reference statements)
13
131
3
7
Order By: Relevance
“…5 Patient follow up also reveals a highly dynamic evolution of these mutations during disease progression in treated and untreated patients. 6,7 This observation is in line with the recent recognition that human tumors harbor an extensive genetic intratumoral heterogeneity.…”
Section: 4supporting
confidence: 73%
“…5 Patient follow up also reveals a highly dynamic evolution of these mutations during disease progression in treated and untreated patients. 6,7 This observation is in line with the recent recognition that human tumors harbor an extensive genetic intratumoral heterogeneity.…”
Section: 4supporting
confidence: 73%
“…23 Notably, selection of mutational profiles was heterogeneous with some patients having no clonal variance during several years, while other had a highly dynamic shift of their mutational profile. 22,36,37 To our knowledge, mutational selection under AZA treatment in therapy-related MDS/AML has not been explored and could have an interest in term of prognosis and prediction of response or relapse. Recently, analysis of clonal selection under AZA treatment before allogeneic stem cell transplantation (allo-SCT) 32 confirmed that AZA could select mutated clones and showed that recurrent clones could re-emerge at relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Median number of cycle was 10 (range 3-15). Median OS was 15 months (range, [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Correlation Between Aza Response and Putative Function Of mentioning
confidence: 99%
See 1 more Smart Citation
“…da Silva-Coelho with colleagues observed that mutational spectrum and CE are influenced by lenalidomide therapy. 49 In general, treatment may…”
Section: Microarray Analysismentioning
confidence: 99%